2015
DOI: 10.1590/1413-785220152306149049
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age on delayed surgical treatment of proximal femoral fractures

Abstract: OBJECTIVE: To investigate the influence of patients' age on the delay between diagnosis and surgical treatment of proximal femoral fracturesMETHODS: This is a retrospective study, con-ducted at a tertiary university hospital, including all patients admitted with proximal femoral fractures between March 2013 and March 2014. The participants were categorized into four groups according to age levels. The groups were compared according to demographics, comorbidities, fracture type, trau-ma circumstances, and time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…The present study demonstrated no relation between the prevalence of coccydynia and the patients' occupations. Among our study population, 84.4% of the patients showed good, 7.6% had excellent, and only 1 had fair responses to coccygectomy (3), which chimes in with other previous studies (10)(11)(12)(13)(14)(15).…”
Section: Discussionsupporting
confidence: 90%
“…The present study demonstrated no relation between the prevalence of coccydynia and the patients' occupations. Among our study population, 84.4% of the patients showed good, 7.6% had excellent, and only 1 had fair responses to coccygectomy (3), which chimes in with other previous studies (10)(11)(12)(13)(14)(15).…”
Section: Discussionsupporting
confidence: 90%
“…No mesmo sentido, no estudo de Gomes et al (2015), que avaliou a influência da idade no tempo entre o diagnóstico e o tratamento cirúrgico de pacientes acometidos por fraturas do fêmur proximal, a principal causa de não adesão à sugestão de cirurgia foi representada por deficiências na estrutura e/ou função do fêmur proximal. O atraso na cirurgia se deu por motivos como indisponibilidade de horário, de falta de sala cirúrgica no dia agendado, de equipe de anestesiologia insuficiente, falta de leitos de terapia intensiva no pós-operatório ou falta de equipamentos suficientes para realizar a cirurgia.…”
Section: Discussionunclassified
“…É essencial monitorar os idosos que já sofreram quedas e identificar os fatores de risco para prevenir futuros eventos. Em suma, a reabilitação eficaz requer uma abordagem abrangente que leve em consideração as necessidades individuais e os desafios específicos enfrentados pelos pacientes idosos (Gomes et., al., 2015).…”
Section: Papel Da Fisioterapia Na Reabilitação Pós-fratura De Fêmurunclassified